Trends over time in the incidence of congenital anophthalmia, microphthalmia and orbital malformation in England: database study. Issue 6 (6th September 2016) - Dharmasena, Aruna; Keenan, Tiarnan; Goldacre, Raph; Hall, Nick; Goldacre, Michael J
Abstract : Aims: To study trends over time in the incidence of congenital anophthalmia, microphthalmia and orbital malformations in England, along with changes in hospital admission rates for these conditions. Methods: Using English National Hospital Episode Statistics (1999–2011), the annual rate of hospital admissions related to anophthalmia, microphthalmia and congenital malformations of orbit/lacrimal apparatus was calculated per 100 000 infants. The records were person-linked, which enabled patients' 'first record' rates to be calculated as proxies for incidence. Similar analyses on pre-1999 datasets were also undertaken for microphthalmia. Results: There was no systematic increase or decrease over time in the incidence of these conditions, but there was some fluctuation from year to year. The incidence of congenital anophthalmia ranged from 2.4 (95% CI 1.3 to 4.0) per 100 000 infants in 1999 to 0.4 (0 to 1.3) in 2011. The annual incidence of congenital microphthalmia was 10.8 (8.2 to 13.5) in 1999 and 10.0 (7.6 to 12.4) in 2011. The annual incidence of congenital orbital/lacrimal malformations was 0.5 (0 to 1.1) in 1999 and 0.7 (0 to 1.4) in 2011. Including multiple admissions per person, admission rates for microphthalmia showed a linear increase over time from 1999. The earlier data for microphthalmia indicated an increase in admission rates, but no change in incidence, from 1971 to 2011. Conclusions: The incidence of these conditions has remained stable in England in recent years. Although the incidence of microphthalmia was stable, hospital admission rates for it increased over time reflecting an increase in multiple admissions per affected person. These data may be useful for planning service provision.